Polycystic ovary syndrome and MTHFR gene C677T and A1298C polymorphisms - Bayram, B.; Kiliççi, C.; Önlü, H.; Şahin, F. (My University, 2010)
In this study, it was aimed to determine the allele frequencies and genotype distributions of MTHFR gene C677T and A1298C polymorphisms in a Turkish study population with polycystic ovary syndrome. Genomic DNA was isolated from blood samples of 30 patients with polycystic ovary syndrome and 28 healthy controls. PCR-RFLP technique was used to analyze MTHFR gene C677T and A1298C polymorphisms. Products of PCR-RFLP technique were assessed with UV transilluminator by being exposed to agarose gel electrophoresis. According to MTHFR gene C677T polymorphism, TT genotype was found statistically higher (p<0.05) in the control group than in the patient group, but allele frequencies were similar between the two groups. Genotype distribution of MTHFR gene A1298C polymorphism between the groups did not show any difference, but according to allele frequencies A allele frequency was statistically higher (p<0.05) in the control group than in the patient group. As a result of this study, it can be concluded that MTHFR gene C677T and A1298C polymorphisms are not involved in polycystic ovary syndrome in this Turkish study population.
Keywords: A1298C; C677T; MTHFR gene; Polycystic ovary syndrome; Polymorphism